Association between preoperative exercise tolerance and unplanned readmission in patients who underwent pancreatectomy for pancreatic ductal adenocarcinoma: a retrospective analysis - Makoto Onji; Shingo Kozono; Asuka Nakai; Shinji Kakizoe; Takaaki Tatsuguchi; Koichi Naito (BMC Cancer)
Abstract Background Despite advances in treatment, the incidence of postoperative complications following pancreatectomy remains high, leading to frequent hospital readmissions. Therefore, this study aimed to investigate the relationship between preoperative exercise tolerance and the likelihood of unplanned readmission in patients with pancreatic ductal adenocarcinoma. Methods This retrospective analysis included 88 patients who underwent pancreatectomy at a single institution between July 2019 and September 2022 and focused on patients with pancreatic ductal adenocarcinoma. Patients’ preoperative exercise tolerance was assessed using the 6-minute walk distance (6 MWD). Results The study found a 22.7% readmission rate within 1 year, with the median 6 MWD being significantly lower in readmitted patients than in those who were not readmitted (390.0 m versus 436.5 m; p < 0.01). A 6 MWD cut-off of 425 m was a strong predictor of readmission, with lower preoperative exercise tolerance associated with a higher risk of readmission. Conclusions Enhancing preoperative physical reserves through exercise therapy may reduce readmission rates and improve patient outcomes. Further research with larger sample sizes is required to confirm these findings.